Effect of Slc35b4 knockdown on total and O-glycosylated cellular proteins in HepG2 cell line. (c2012) - Antonios, Gregory (2012)
Diabetes is considered a Non-Communicable Disease (NCD). Type II diabetes is caused by the lack of insulin production from liver beta cells in the aftermath of insulin resistance. Slc35b4 encodes a protein that transports UDP-xylose and UDP-N-acetylglucosamine from the cytosol into the golgi. UDP-N-acetylglucosamine then serves as both a substrate for O-linked glycosylation (O-GlcNAC) and as a negative feedback inhibitor of the Hexosamine Biosynthesis Pathway (HBP) pathway. Solute receptor SLC35b4 has been identified, using both genetic and functional studies, as a regulator of obesity, insulin resistance and gluconeogenesis by Yazbek et al. Over 600 proteins are modified with the addition of an O-GlcNAC moiety and may therefore contribute to the phenotype. This study employs One Dimensional (1D) and Two Dimensional (2D) electrophoresis to investigate differentially expressed O-glycosylated and total proteins in a HepG2 (Human liver carcinoma cell line) SLC35b4 knockdown cell line. Western blot analysis, using a primary antibody against O-glycosylated proteins, showed one differentially expressed O-glycosylated protein in a HepG2 cell line knockdown of SLC35b4. Its size was estimated to be 67.5 kDa. The 2D electrophoresis study of SLC35b4 knockdown resulted in the differential expression of 10 proteins, more than 2 fold, as compared to control siRNA. Moreover, 3 of the differentially expressed proteins (corresponding to Spots SSP 6203, 6204 and 8102) have very close matches in O-glycosylated proteins of the insulin resistance pathway where O-glycosylation might play a role in glucose synthesis. The identification of the differentially expressed protein is a must in order to assess SLC35b4 role in the insulin resistance (IR) pathway using its knockdown.